Pushover Analysis of Ageing Offshore Jacket Platform in Shallow Water Under Extreme Storm and Mitigation Strategy for Platform’s Life Extension - Setiawan, Budi; Rosyid, Daniel Mohammad; Prastianto, Rudi Walujo (Institut Teknologi Sepuluh Nopember, 2025)
Many offshore jacket platforms worldwide have approached or exceeded their original design life but are still in use and productive. According to the international codes, standards, and industry best practices, structural assessments of ageing fixed offshore jacket platforms shall be conducted against relevant target values to assess whether it is fit for purpose or risk reduction measures should be considered for continuing its operation. This research examines the collapse behaviour of an ageing offshore jacket platform under extreme storm conditions. Nonlinear collapse analysis has been performed to assess fixed offshore jacket platforms' structural integrity and reliability in shallow water under extreme storm conditions. Two tripods and 4-legged jacket platforms at water depths between 30 to 80 meters, located in the Mahakam Delta, Kalimantan, Indonesia, have been selected in this research as wellhead platform models commonly installed in shallow water. Sensitivity studies examine the effects of pile-soil interaction, variations in pile depth, topside load adjustments, marine growth removal, and jacket strengthening on structural performance. From the structural integrity and reliability perspective, the findings highlight that strengthening the jacket by adding soldier piles is the most effective approach for extending the platform's lifespan, especially for a wave-dominated platform. Additionally, a cost feasibility analysis is advised for future evaluation to determine whether jacket strengthening is viable or if alternative risk reduction strategies should be further explored for the ageing offshore platform.